Learning Recognition and Credentialing: Expanding Prior Learning Assessment (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2023)
The relationship between formal credentials and employment has long been established. People need officially recognized post-secondary and/or industry credentials, most often tertiary degrees, to obtain employment that provides sustainable, living wages. Data show unemployment rates in the Organisation for Economic Cooperation and Development (OECD) member countries are significantly lower for those with higher degrees, averaging 4% for tertiary education (i.e., postsecondary education) compared to 6% for upper secondary education, and 11% for below upper secondary (OECD, 2022). Those with a tertiary degree earn 50% more than those with an upper secondary education and 100% more than those with below an upper secondary education (OECD, 2022). The United States Bureau of Labor Statistics (USBLS, 2021) reports similar trends: earnings of those with a tertiary degree are almost twice that of those with a high school diploma, and those with some college but no degree earn two and a half times that of those without a high school diploma. Unemployment rates in the United States also reflect the differential between those with and without degrees. In 2021, the average unemployment rate for those with a tertiary degree was 2.8%, while those with a high school diploma is 6.2% and those with less than high school was 8.3% (USBLS, 2021).